Differentiation of five enterohepatic Helicobacter species by nested PCR with high‐resolution melting curve analysis. Issue 2 (30th September 2016) - Wu, Miaoli; Rao, Dan; Zhu, Yujun; Wang, Jing; Yuan, Wen; Zhang, Yu; Huang, Ren; Guo, Pengju
Abstract: Background: Enterohepatic Helicobacter species (EHS) are widespread in rodent species around the world. Several studies have demonstrated that infection with EHS can interfere with the outcomes of animal experiments in cancer research and significantly influence the study results. Therefore, it is essential to establish a rapid detection and identification of EHS for biomedical research using laboratory rodents. Our study aimed to develop a rapid and sensitive method to detect and distinguish five enterohepatic Helicobacter species. Materials and Methods: Nested PCR followed by high‐resolution melting curve analysis (HRM) was developed for identification of H. bilis, H. rodentium, H. muridarum, H. typhlonius, as well as H. hepaticus . To validate the accuracy of nested PCR‐HRM analysis, quantitative real‐time PCR methods for five different enterohepatic Helicobacter species were developed. A total of 50 cecal samples were tested using both nested PCR‐HRM analysis and qPCR method. Results: The nested PCR‐HRM method could distinguish five enterohepatic Helicobacter species by different melting temperatures. The melting curve were characterized by peaks of 78.7 ± 0.12°C for H. rodentium, 80.51 ± 0.09°C for H. bilis, 81.6 ± 0.1°C for H. typhlonius, 82.11 ± 0.18°C for H. muridarum, and 82.95 ± 0.09°C for H. hepaticus . Conclusions: The nested PCR‐HRM assay is a simple, rapid, and cost‐effective assay. This assay could be a useful tool for molecular epidemiology study of enterohepatic Helicobacter infection and an attractive alternative for genotyping of enterohepatic Helicobacter species.